2017
DOI: 10.1109/tbme.2016.2580904
|View full text |Cite
|
Sign up to set email alerts
|

Cuffless Blood Pressure Estimation Algorithms for Continuous Health-Care Monitoring

Abstract: The results indicate that the proposed algorithm for the cuffless estimation of the BP can potentially enable mobile health-care gadgets to monitor the BP continuously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
295
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 443 publications
(339 citation statements)
references
References 31 publications
(33 reference statements)
9
295
3
1
Order By: Relevance
“…In their work, various machine learning-based techniques were compared and they found that non-linear algorithms, like kernel machines or ensemble-learning methods as well as the AdaBoost model, gave better performances than linear approximations. Other techniques such as linear regression and decision tree were found not appropriate in predicting BP [114]. …”
Section: Comparison Between Modelsmentioning
confidence: 97%
See 1 more Smart Citation
“…In their work, various machine learning-based techniques were compared and they found that non-linear algorithms, like kernel machines or ensemble-learning methods as well as the AdaBoost model, gave better performances than linear approximations. Other techniques such as linear regression and decision tree were found not appropriate in predicting BP [114]. …”
Section: Comparison Between Modelsmentioning
confidence: 97%
“…PIR was found mainly dependent on the arterial diameter and correlated with DBP [90,113]. Recently, machine learning-based techniques have been investigated [114] and promising results have been reported. In their work, various machine learning-based techniques were compared and they found that non-linear algorithms, like kernel machines or ensemble-learning methods as well as the AdaBoost model, gave better performances than linear approximations.…”
Section: Comparison Between Modelsmentioning
confidence: 99%
“…We calculated a single target score (the aggregated value using a weighted average of the scores for each signal portion where a score for each signal portion is the median of the top 5% of the highest EMG amplitudes) from these scores as the outcome of each experiment. The simplest approach would have been to average these values [20]; however, many scores were contaminated by noise and some could have been limited by subject effort. Accordingly, using a simple average or median of scores may not be an accurate measure of the real expected target values.…”
Section: Methodsmentioning
confidence: 99%
“…In machine learning methods, it is provided to produce output values for different inputs by training the corresponding output values of certain input values. Models such as random forest [115,116], regression tree [117], support vector machines [118], K-nearest neighbors, and deep learning [119] are used in the analysis of blood pressure measurements. There is a standard of IEEE on wearable blood pressure gauges [120].…”
Section: Prediction Algorithms Used For Predicting Blood Pressure Usimentioning
confidence: 99%